J05 Legato-hd study: a phase 2 study assessing the efficacy and safety of laquinimod as a treatment for huntington disease. (September 2018) - Reilmann, Ralf; Gordon, Mark Forrest; Anderson, Karen E; Feigin, Andrew; Tabrizi, Sarah J; Leavitt, Blair R; Stout, Julie C; Piccini, Paola; Rynkowski, Gail; Volkinshtein, Rita; Savola, Juha
Abstract : Introduction: Laquinimod (Teva Pharmaceuticals) is an orally active small molecule that passively enters the blood brain barrier and has been shown to upregulate BDNF secretion and modulate CNS-resident inflammatory pathways involved in pathology of HD. The LEGATO-HD study originally included three dose arms, 0.5 mg, 1.0 mg and 1.5 mg versus placebo in a 12-month multicenter double blind phase 2 study in patients with HD. Cardiovascular safety concerns were observed in multiple sclerosis studies with laquinimod doses of 1.2 mg and 1.5 mg. Although no similar concern was identified in LEGATO-HD, Teva discontinued the 1.5 mg arm in January 2016 as a precautionary safety measure and continued to evaluate the efficacy and safety of the 0.5 mg and 1.0 mg doses. Aims: Evaluate the efficacy and safety of laquinimod in patients with Huntington Disease (HD). Methods: Efficacy assessments include the primary endpoint, change from baseline in Unified Huntington's Disease Rating Scale Total Motor Score (UHDRS-TMS) at month 12, and the secondary endpoint, percent change in caudate volume at month 12. Safety measures include adverse event reporting, clinical laboratory tests, vital signs, ECGs, physical examinations, and suicidality (C-SSRS). Results: LEGATO-HD is fully enrolled with 352 patients randomized and is expected to complete in June 2018. Baseline mean (SD) pooled demographics of enrolled patients include females n=172 (49.1%), males n=178 (50.9%), age 44.4(7.6) years, UHDRS-TMS 24.3(13.1), UHDRS-Total Functional Capacity (TFC) 11.1(1.7), and UHDRS-Functional Assessment (FA) 22.7(2.4). The results of the primary and secondary efficacy endpoints and safety measures will be presented at the conference. Conclusion: There is a significant unmet medical need to ameliorate the progression of symptoms and the neurodegeneration in HD. LEGATO-HD provides valuable information towards understanding the efficacy and safety of laquinimod as a potential treatment for patients with HD. The LEGATO-HD Study is sponsored by Teva Pharmaceuticals Ltd in collaboration with HSG and EHDN and is registered as NCT02215616 -clinicaltrials.gov and 2014–000418–75-EudraCT.